2023
DOI: 10.21873/anticanres.16201
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial–Mesenchymal Transition Phenotype and Peritumoral Immune Cell Infiltration in Advanced Biliary Tract Cancer

Abstract: We evaluated the clinical implications of epithelial-mesenchymal transition (EMT) markers and peritumoral immune cell in ltration in patients with biliary tract cancer (BTC) treated with gemcitabine plus cisplatin (GemCis). Forty-ve patients with advanced BTC who received GemCis were included as the study population. We conducted multiplex immunohistochemistry and examined EMT markers and their correlations with immune cell in ltrate at the invasive tumor margin. Study population was subdivided into two groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The involvement of EMT processes in cholangiocarcinoma has been proposed previously [ 36 , 37 ]. Moreover, consistent over-expression of EMT-related features has been shown to correlate with poor prognosis in advanced BTC [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of EMT processes in cholangiocarcinoma has been proposed previously [ 36 , 37 ]. Moreover, consistent over-expression of EMT-related features has been shown to correlate with poor prognosis in advanced BTC [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, one study has demonstrated that CD4 + T-cell infiltration at the tumor edge is significantly higher than in the tumor center in both ICCA and extrahepatic CCA (eCCA) [ 18 ]. The BTC tumor edge serves as the primary location for active infiltration by FOXP3 + CD4 + Tregs that express elevated levels of lymphocyte activation gene 3 ( LAG-3 ) and T cell immunoglobulin and mucin domain-containing protein 3 ( TIM3 ) [ 33 , 34 ]. Furthermore, a high density of FOXP3 – CD4 + Th cells at the tumor edge is independently associated with longer PFS and OS in patients undergoing palliative gemcitabine plus cisplatin treatment [ 33 ].…”
Section: Immune Landscape In Ccamentioning
confidence: 99%
“…The BTC tumor edge serves as the primary location for active infiltration by FOXP3 + CD4 + Tregs that express elevated levels of lymphocyte activation gene 3 (LAG-3) and T cell immunoglobulin and mucin domain-containing protein 3 (TIM3) [33,34]. Furthermore, a high density of FOXP3 -CD4 + Th cells at the tumor edge is independently associated with longer PFS and OS in patients undergoing palliative gemcitabine plus cisplatin treatment [33]. Conversely, another study has found no significant difference in the distribution of CD4 + T cells between the peritumoral and intratumoral regions [35].…”
Section: Proportions and Distribution Of Cd4 + T Cells In Ccamentioning
confidence: 99%
See 1 more Smart Citation